PENGARUH MODEL QUIS DAN GAYA BELAJAR VISUAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS VIII MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TOPIK SENI ISLAMI DI SMPN 1 JABON - Ninik Rahayu; Danu Rusmawati, Retno; Hartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The purpose of this study was to determine the results of the test: (1) The Influence Between the Quiz Model and the lecture method on Students' PAI learning achievement, (2) The Influence Between High and Low Visual Learning Styles on Students' PAI learning achievement, (3) Interaction Between the Quiz Model and Visual Learning Style on Students' PAI learning achievement of VIIIth graders at SMPN 1 Jabon. This experimental research was conducted using a 2x2 factorial design. The subjects in this study were students of grade XI consisting of four classes with 120 students of grade VIII at SMPN 1 Jabon. The subjects that were the focus of the experiment were taken randomly by classical sampling, namely four classes ABCD from grade VIII at SMPN 1 Jabon. The hypothesis of this study was tested using the Analysis of Variant (Anova) statistical test. (1) PAI learning achievement of students taught with the Quiz Model By comparing the probability value, namely 0.001 with the significance level or α, namely 0.05. Based on the table, it turns out that 0.001 < 0.05, so it can be said to be significant. Thus, it can be said that the Quiz Model and lecture method affect the PAI learning achievement of grade VIII students at SMPN 1 Jabon, (2) PAI learning achievement of students who have a high Visual Learning Style and have a low Visual Learning Style By comparing the probability value, namely 0.001 with the significance level or α, namely 0.05. Based on the table, it turns out that 0.001 < 0.05, so it can be said to be significant. Thus, it can be said that the PAI learning achievement of students who have a high Visual Learning Style affects the PAI learning achievement when compared to those who have a low Visual Learning Style of class VIII students at SMPN 1 Jabon, and (3). Based on the table, it turns out that 0.001 < 0.05, so it can be said that there is an interaction between the Quiz Model, lecture method, and Visual Learning Style on the PAI learning achievement of class VIII students at SMPN 1 Jabon. Based on the results of the study, it was concluded that using the Quiz Model and Visual Learning Style can improve the PAI learning achievement of class VIII students at SMPN 1 Jabon. Keywords: Quis Model, Learning Style, Learning Achievement.